Pedagogical spaces in the teaching of Physical Education: Implications in a federal educational institution. (Research, Society and Development, 2020)
The present study aimed qualitatively to analyze, from the perspective of the institution's Physical Education, the questions regarding the structure of the discipline's physical spaces on the campuses of a Federal Teaching Institution (IFES) located in the state of Piauí, Brazil and its implications for the school curriculum and the education of students. The survey included structural verification through a survey of the physical structures available for teaching Physical Education on each campus of this institution through the website of the same IFES, the Institutional Development Plan 2015 to 2019 (PDI) and consultation with teachers of Physical Education on campuses through the WhatsApp Messenger instant messaging application, the integrated high school course plans offered by this institution in Administration, Informatics, Agriculture, Buildings, Environment, Electronics, Fruit and Electromechanics and their respective Physical Education courses were also observed. According to the data of the present study, we can observe through institutional documents that there is no harmony between the structure of the campuses and the Physical Education discipline menu, leaving the teacher to prioritize or not the contents that are viable for learning.